1.Przekształć wyrażenia do najprostszej postaci.

1.7xy + ( 5x - 2x + xy ) =
2.-2x + ( -6xy + 4x -y) =
3.y-(-2y + 8x - 3xy) =
4.-6 xy - (2xy - 3x + 4y ) =
5.( -2x + 3x - 1 ) + ( -3x <do kwadratu> + 2 x -1 )=
6.(11 r - 6 s -r<do kwadratu>s ) - (- r <do kwadratu> s + 5 s - 11 r)=

2

Odpowiedzi

2010-03-23T20:06:38+01:00
1.7xy + ( 5x - 2x + xy ) = 7xy + 3x +xy= 8xy +3x

2.-2x + ( -6xy + 4x -y) = 2x -6xy -y

3.y-(-2y + 8x - 3xy) = 3y +8x - 3xy

4.-6 xy - (2xy - 3x + 4y ) = --8xy -3x + 4y

5.( -2x + 3x - 1 ) + ( -3x <do kwadratu> + 2 x -1 )= (x-1 ) +(11x - 1)=12x -2

6.(11 r - 6 s -r<do kwadratu>s ) - (- r <do kwadratu> s + 5 s - 11 r)= a tego nie wiem xD
2 1 2
2010-03-23T20:10:22+01:00
1.7xy + ( 5x - 2x + xy ) = 7xy+5x-2x+xy=8xy+3x
2.-2x + ( -6xy + 4x -y) = -2x-6xy+4x-y= 2x-6xy-y
3.y-(-2y + 8x - 3xy) = y+2y-8x+3xy= 3y-8x+3xy
4.-6 xy - (2xy - 3x + 4y ) = -6xy-2xy+3x-4y= -8xy+3x-4y
5.( -2x + 3x - 1 ) + ( -3x² + 2 x -1 )= -2x+3x- 1-3x²+2x-1= 3x-2-3x²
6.(11 r-6s-r²s)-(- r ²s + 5s-11r)= 11r-6s-r²s+r²s+5s-11r= -s
1 1 1